Chorea-Acanthocytosis Genotype in the Original Critchley Kentucky Neuroacanthocytosis Kindred - Velayos-Baeza, A; Holinski-Feder, E; Neitzel, B; Bader, B; Critchley, E; Monaco, A; Danek, A; Walker, R (2011)
Objective: Todetermine the molecular nature of the neurological disease in the seminal family reported by Critchley et al inthe 1960s, characterized by a hyperkinetic movement disorder and the appearance of acanthocytosis on peripheral blood smear. The eponym Levine-Critchley syndrome, subsequently termed neuroacanthocytosis, has been applied to symptomatically similar, but genetically distinct, disorders, resulting in clinical and diagnostic confusion. Design: DNA analysis. Setting: Molecular biology research laboratories. Participants: First- and second-degree relatives of the original Critchley et al proband from Kentucky. Main Outcome Measures: Mutations in the VPS13A gene. Results: A mutation was identified in the VPS13A gene, responsible for autosomal recessive chorea-acanthocytosis. Haplotype reconstruction suggested that this mutation was homozygous in the proband. Conclusion: These findings strongly support the diagnosis of chorea-acanthocytosis as the disorder described in the original report. ©2011 American Medical Association. All rights reserved.